SIMPLE SKILLS SECRETS: A VISUAL MODEL OF CORE COMMUNICATION SKILLS FOR GENERIC STAFF. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Groves, Karen; Jack, Barbara; Baldry, Cath; O'Brien, Mary; Marley, Kate; Whelan, Alison; Kirton, Jenny
Abstract : Background: Every healthcare worker, of any grade or role, can be faced with situations they find difficult to handle, particularly in end of life situations. Rolling out communication skills training to large numbers of people is a challenge. The 'Simple Skills Secrets' model was developed to provide an easily remembered visual model for any staff member, in any setting or situation where faced with unanswerable questions or lost for words. The model distils the essence of safely responding to cues, listening, encouraging, summarizing and assisting the formulation of the patient's own plan whilst resisting the urge to rush in with solutions. Aims: To assess the impact of a 'Simple Skills Secrets' model of communication skills training on staff confidence and willingness. Method: A mixed methods evaluation of impact on staff who had undertaken training included pre and post course assessment of confidence and willingness for 149, and qualitative interviews of fourteen, 6–8 weeks post course, using a purposive sampling approach. Results: Statistically significant improvement in both willingness and confidence for all categories and staff of all grades. (Overall confidence score, t(148)=–15.607, p=<0.05; overall willingness score t(148)=–10.878, p=<0.05). Greatest confidence change was in communicating with carers (pre course mean 6.171; post course mean 8.171). The value of the model in clinical practice was reported and several themes emerged from the qualitative data including: a method of communicating differently, a structured approach, an easy to remember visual model, thinking differently, increased confidence, using small amounts of time effectively, gaining additional skills and helping the person come up with answers themselves. Conclusions: This model appears to be easily remembered, increase staff confidence and willingness to engage which may result in earlier, shorter, interventions, minimizing distress, improving patient and carer satisfaction.